(untitled) (Tanzania Medical Journal, 2016)
Endometrial ossification is uncommon condition which is related to secondary infertility following abortion. It is characterized by the presence of mature or metaplastic bone formation in the endometrium. There are about 100 cases that have been reported in the literature to date. Its etiology and pathogenesis is controversial and several debatable assumptions have been described in the literature. We present an additional case of endometrial ossification of a 32 years old female who presented with history of uterine Caesarian section delivery five years ago. She later had abortion of 14 months of gestation two years after Caesarian delivery. One year later after abortion, during pre conception examination, a mass was found in the uterus which was not treated until when she was referred to our hospital. Ultrasonography examination revealed a hyperechoic mass which size was 3.6×0.8cm, extending from lower uterine segment to endocervix. The mass was resected with uneventful recovery. The resected tissues were subjected for histological analysis where the diagnosis of endometrial ossification was made on histopathology which showed endometrial tissue intermingled with bony tissue.Few months later she conceived and delivered normally a full tem healthy baby boy. The removal of bone fragments by curettage is very likely to bring about natural conception in patients with endometrial ossification.